ADCK3 mutations with epilepsy, stroke‐like episodes and ataxia: a POLG mimic?. (23rd April 2016) - Hikmat, O.; Tzoulis, C.; Knappskog, P. M.; Johansson, S.; Boman, H.; Sztromwasser, P.; Lien, E.; Brodtkorb, E.; Ghezzi, D.; Bindoff, L. A.
Abstract : Background and purpose: Defects of coenzyme Q10 (CoQ10) metabolism cause a variety of disorders ranging from isolated myopathy to multisystem involvement. ADCK3 is one of several genes associated with CoQ10 deficiency that presents with progressive cerebellar ataxia, epilepsy, migraine and psychiatric disorders. Diagnosis is challenging due to the wide clinical spectrum and overlap with other mitochondrial disorders. Methods: A detailed description of three new patients and one previously reported patient from three Norwegian families with novel and known ADCK3 mutations is provided focusing on the epileptic semiology and response to treatment. Mutations were identified by whole exome sequencing and in two measurement of skeletal muscle CoQ10 was performed. Results: All four patients presented with childhood‐onset epilepsy and progressive cerebellar ataxia. Three patients had epilepsia partialis continua and stroke‐like episodes affecting the posterior brain. Electroencephalography showed focal epileptic activity in the occipital and temporal lobes. Genetic investigation revealed ADCK3 mutations in all patients including a novel change in exon 15: c.T1732G, p.F578V. There was no apparent genotype−phenotype correlation. Conclusion: ADCK3 mutations can cause a combination of progressive ataxia and acute epileptic encephalopathy with stroke‐like episodes. The clinical, radiological and electrophysiological features of this disorder mimic the phenotype of polymerase gamma (POLG) related encephalopathy and it is therefore suggested that ADCK3 mutations be considered in the differential diagnosis of mitochondrial encephalopathy with POLG‐like features.